THE INFLUENCE of SHORT-HEATING-CYCLE INVESTMENTS on THE QUALITY of COMMERCIALLY PURE TITANIUM CASTINGS - Nogueira, Fabiane [UNESP]; Grassi Fais, Laiza Maria [UNESP]; Fonseca, Renata Garcia [UNESP]; Adabo, Gelson Luis [UNESP] (Mosby-elsevier, 2010)
Statement of problem. A new short-cycle, spinel-based investment was developed to minimize the long heating cycle generally required for conventional investments for titanium castings, but the quality of castings made using this material has yet to be evaluated.Purpose. The purpose of this study was to compare the Vickers hardness, castability, surface roughness, in vitro marginal misfit, and internal porosity of castings made using silica phosphate-based and spinel-based investments.Material and methods. The specimens were commercially pure titanium cast using silica phosphate-based investment, Rematitan Plus (RP), and spinel-based investments, Rematitan Ultra (RU) or short-heat-cycle Trinell (TR). Disc-shaped patterns (6 x 3 mm) were cast, and Vickers hardness was measured at the surface, and 50, 100, 150, and 200 pm beneath the surface (n=10). Microstructure was analyzed by optical microscopy (x100). Mesh patterns (14 x 14 x 0.5 mm) were used for castability testing (n=10). Surface roughness (Ra) was measured on disc-shaped patterns (13 x 3 mm) with a profilometer (n=8). Wax copings were cast, screwed to implant abutments, and the marginal misfit was measured using image analysis software (n=10). Internal porosity of the copings was evaluated by density comparisons (n=10). Hardness data were analyzed by 2-way ANOVA and the Tukey HSD test. Castability, surface roughness, and marginal misfit were analyzed by 1-way ANOVA and the Tukey HSD test, and internal porosity by Kruskal-Wallis and Student-Newman-Keuls tests (alpha=.05).Results. RP had the highest hardness values at the surface and 50 pm beneath, but the hardness values of TR, RU, and RP were statistically equivalent at 100, 150, and 200 mu m. Significant differences were seen when comparing RU and TR with RP for castability (P<.001), surface roughness (P<.001), and marginal misfit (P<.001). No significant differences were seen for internal porosity.Conclusions. The quality of castings made from the new investment, TR, was similar to the quality of those made using the conventional spinel-based investment, RU, and superior to those made using RP. (J Prosthet Dent 2010; 104:265-272)